2010
DOI: 10.1525/cond.2010.100149
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Ecology of the Rusty Blackbird in Alaska and Canada

Abstract: Resumen. examinamos la ecología de nidificación de Euphagus carolinus a través del monitoreo de 162 nidos para obtener datos de supervivencia de nidos en alaska y de 252 registros adicionales de alaska y canadá para identificar habitats importantes para la nidificación y evaluar si las bajas tasas de éxito de nidos contribuyeron a las disminuciones poblacionales en alaska. en la costa de alaska y a lo largo de canadá, los nidos se encontraron principalmente en coníferas (85% de 212 nidos). todos los nidos en c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 37 publications
(15 reference statements)
1
26
0
Order By: Relevance
“…We conducted our rapid surveys between 06:00 and 13:00 and from 11 to 23 May, the period from pair formation to early incubation (Matsuoka et al 2010) and the time when we expected detection rates to be relatively high because most females would not yet be incubating their eggs and most males would still be actively singing and closely guarding their mates. We did not constrain our surveys to the early morning because previous work indicated that detectability of breeding Rusty Blackbirds does not vary over the morning (P. Blancher, unpubl.…”
Section: Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted our rapid surveys between 06:00 and 13:00 and from 11 to 23 May, the period from pair formation to early incubation (Matsuoka et al 2010) and the time when we expected detection rates to be relatively high because most females would not yet be incubating their eggs and most males would still be actively singing and closely guarding their mates. We did not constrain our surveys to the early morning because previous work indicated that detectability of breeding Rusty Blackbirds does not vary over the morning (P. Blancher, unpubl.…”
Section: Field Methodsmentioning
confidence: 99%
“…Surface water is largely limited to ponds, lakes, and estuaries and nearby areas with shallow water and emergent wetland vegetation. The plant species in Anchorage wetlands are similar to those on the Tanana Flats, but black spruce is more common and willows ( 1 m in height) are less common (Matsuoka et al 2010). At Anchorage, all wetlands were accessible by road, foot, or canoe.…”
Section: Study Areamentioning
confidence: 95%
“…Matsuoka et al (2010a) and Powell et al (2010a) respectively surveyed and radio-tracked breeding Rusty Blackbirds and found that the generally low breeding densities observed over much of the species' range are linked to specialized use of shallow-water habitats for foraging and large home ranges, which typically include multiple wetlands used for foraging and nesting. Matsuoka et al (2010b) and Powell et al (2010b) analyzed data from >450 nests across the breeding range and showed that the species' widespread use of small stunted conifers, primarily spruce (Picea spp. ), for nest sites is selective and leads to relatively high rates of nest survival when nests are placed in undisturbed wetlands in Alaska and New England.…”
Section: Important Findings Of the Special Sectionmentioning
confidence: 99%
“…Thus, buffers from logging around wetlands ought to be explored as a conservation measure to protect nesting Rusty Blackbirds from these negative consequences (Powell et al 2010b). Average rates of nest success in Alaska (56%; Matsuoka et al 2010b) and New England (62%; Powell 2008) are not at chronically low levels that could be linked to long-term declines, so factors reducing survival of adults or juveniles are likely limiting population growth (Matsuoka et al 2010b). Luscier et al (2010) conducted the first formal surveys targeting wintering Rusty Blackbirds and modeled occupancy to show that birds wintering in the lower Mississippi Alluvial Valley are commonly found in a variety of forested wetlands but often are observed in adjacent agricultural fields, where they sometimes feed in loose association with other blackbirds.…”
Section: Important Findings Of the Special Sectionmentioning
confidence: 99%
See 1 more Smart Citation